Hadith #2322 - Sunan Abi Dawud - Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu Bakra al-Thaqafi; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
We kept fast for twenty-nine days along with the Prophet (ﷺ) more often than we kept fast for thirty days.
Grade: Sahih

Hadith #2414 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; al-Hasan al-Basri الحسن البصري; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Ibn ‘Umar used to go out to al-Ghabah (jungle), but he neither broke his fast, nor shortened his prayer.
Grade: Sahih

Hadith #2759 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; Ayana bin 'Abdur rahman bin Jushan عيينة بن عبد الرحمن بن جوشن; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Sulaym ibn Amir, a man of Himyar, said: There was a covenant between Mu’awiyah and the Byzantines, and he was going towards their country, and when the covenant came to an end, he attacked them. A man came on a horse, or a packhorse saying, Allah is Most Great, Allah is Most Great; let there be faithfulness and not treachery. And when they looked they found that he was Amr ibn Abasah. Mu’awiyah sent for him and questioned him (about that). He said: I heard the Messenger of Allah (ﷺ) say: W
Grade: Sahih

Hadith #2773 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري (Sunan Abi Dawud)
Ka’ab bin Malik said “When the Prophet(ﷺ) arrived from a journey, he first went to a mosque where he prayed two rak’ahs after which he sat in it and gave audience to the people. The narrator Ibn Al Sarh then narrated the rest of the tradition. He said “The Apostle of Allaah(ﷺ) forbade the Muslims to speak to any three of us. When considerable time had passed on me, I ascended the wall of Abu Qatadah who was my cousin. I saluted him, but, I swear by Allaah he did not return my salutat
Grade: Sahih

Hadith #3588 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu Bakra al-Thaqafi; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) gave the decision that the two adversaries should be made to sit in front of the judge.
Grade: Da'if

Hadith #4441 - Sunan Abi Dawud - Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu Bakra al-Thaqafi; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The word shukkta means tied, meaning her clothes were tied on her.
Grade: Sahih

Hadith #4632 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; al-Hasan al-Basri الحسن البصري; Ash'uth bin Qays; Muhammad bin 'Abdullah al-Ansari محمد بن عبد الله بن المثني - الأنصاري; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
Abu Hurairah said that a man came to the Messenger of Allah (ﷺ) and said: I saw (in my dream) a piece of cloud from which ghee and honey were dropping. I saw the people spreading their hands. Some of them took much and some a little. I also saw a rope hanging from Heaven to Earth. I saw, Messenger of Allah, that you caught hold of it and ascended by it. Then another man caught hold of it and ascended it. Then another man caught hold of it and ascended it. Then another man caught hold of it, bu
Grade: Sahih

Hadith #4633 - Sunan Abi Dawud - Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu Bakra al-Thaqafi; Ali bin Zayd bin 'Abdullah bin Zuhayr علي بن زيد بن عبد الله بن زهير; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
He refused to tell him (his mistake).
Grade: Sahih

Hadith #4660 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; al-Hasan al-Basri الحسن البصري; Ali bin Zayd bin 'Abdullah bin Zuhayr علي بن زيد بن عبد الله بن زهير; Ash'uth bin Qays; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin 'Abdullah al-Ansari محمد بن عبد الله بن المثني - الأنصاري; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
When the illness of the Messenger of Allah (ﷺ) became serious while I was with him among a group of people, Bilal called him for prayer. He said: Ask someone to lead the people in prayer. So Abdullah ibn Zam’ah went out and found that Umar was present among the people and AbuBakr was not there. I said: Umar, get up and lead the people in prayer. So he came forward and uttered “Allah is Most Great”. When the Messenger of Allah (ﷺ) heard his voice, as Umar had a loud voice, he said: Wher
Grade: Hasan Sahih

Hadith #4803 - Sunan Abi Dawud - Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu Bakra al-Thaqafi; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Musa bin Nafi', Abu Shahab al-Hanat موسى بن نافع الأسدي أبو شهاب الحناط (Sunan Abi Dawud)
It is Allah’s right that nothing should become exalted in the world but he lowers it.
Grade: Sahih

Hadith #4900 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; Ayana bin 'Abdur rahman bin Jushan عيينة بن عبد الرحمن بن جوشن; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) said: Make a mention of the virtues of your dead, and refrain from (mentioning) their evils.
Grade: Da'if